Benthaminin 3, a Novel Antibacterial Cassane-Type Furanoditerpenoid from Caesalpinia benthamiana - Rita A. Dickson,; Kofi Annan,; Theophilus C. Fleischer ,; Peter J. Houghton, (Journal of Pharmacy and Nutrition Sciences, 2012)
The roots of Caesalpinia benthamiana (synonym. Mezoneuron benthamianum)are considered to be an effective remedy in Ghana for the management of skin diseases and wounds. Bioactivity-guided fractionation of the chloroform extract of the root bark of the plant has resulted in the isolation of a novel cassane-type furanoditerpenoid, designated as benthaminin 3. The structure of the compound was elucidated by the use of spectroscopic techniques. The antibacterial activity of the compound has been assessed using the microdilution assay method. The lowest MIC (63μg/mL) was recorded against Staphylococcus aureus and Bacillus subtilis. The compound wasalso observed to have a mild inhibitory effect against resistant strains of bacteria including methicillin-resistant S. aureus, tetracyline-resistant S. aureus and erythromycin-resistant S. aureus with MIC values greater than 1000μg/mL.